Участь у сільськогосподарських кооперативах: стимулюючі та стримуючі чинники - Пантелеймоненко, А. О.; Гончаренко, В. В.; Довгаль, О. А.; Panteleimonenko, A.; Honcharenko, V.; Dovgal, O. (ЦНТУ, 2022)
Акцентовано, що у сучасній українській економічній науці відсутні праці, що комплексно відображають і стимулюючі, і стримуючі чинники щодо організації та функціонування українських сільськогосподарських сервісних (обслуговуючих) кооперативів. На основі результатів роботи з фокус-групами фермерів Полтавської області, визначено названі чинники, а також представлено науково-практичні коментарі до кожного з них. Серед основних стимулюючих чинників, що обумовлюють потребу участі в сільськогосподарських сервісних (обслуговуючих) кооперативах виділено низький рівень сільськогосподарських, економічних та правових знань у дрібних сільськогосподарських товаровиробників. Підкреслено, що потребу в кооперуванні посилює відсутність власних коштів та доступу до кредитних ресурсів на господарські потреби, а також до віддалених ринків збуту та брак об’єктивної інформації про вигідних постачальників. It is emphasized that in modern Ukrainian economic science there are no works that comprehensively reflect both stimulating and restraining factors regarding the organization and functioning of Ukrainian agricultural servicing cooperatives. Based on the results of work with focus groups of farmers in Poltava region, these factors are identified, as well as scientific and practical comments on each of them are presented. The high level of agricultural, economic and legal knowledge of small agricultural producers is among the main stimulating factors that determine the need to participate in agricultural servicing cooperatives. It is emphasized that the need for cooperation is exacerbated by the lack of own funds and access to credit resources for economic needs, as well as to remote markets and the lack of objective information about profitable suppliers. Important stimulating factors include the low level of trust of farmers and small agricultural producers in various types of external support: state, foreign technical assistance and assistance from domestic farmers' representative organizations.
Participation in Agricultural Cooperatives: Stimulating and Restraining Factors
Keywords: кооперативи; сільськогосподарські сервісні кооперативи; фермери; cooperatives; agricultural service cooperatives; farmers